Of the Human Condition : Hope and Despair at the End of the Century. - Ashiya City Museum of Art and History, Ashiya; Nanjo, Fumio (Tokyo : Spiral/Wacaol Art Center, 1994)
Africano, Nicolas ; Barney, Matthew ; Boetti, Alighiero ; Boltanski, Christian ; Foulkes, Llyn ; Gilbert & George ; Goldin, Nan ; Kienholz, Ed & Nancy ; Lafont, Suzanne ; Lewis, Mark ; Othoniel, Jean-Michel ; Rath, Alan ; Rockman, Alexis ; Samba, Chéri ; Smith, Kiki ; Teraoka, Masami ; Viola, Bill ; etc.
Of the Human Condition : Hope and Despair at the End of the Century, Spiral/Wacaol Art Center, Tokyo, February 1 - 20, 1994 ; Ashiya City Museum of Art and History, Ashiya, April 9 - May 29, 1994
English-Japanese
kunstcatalogus